NATIVE SILICON ASSOCIATED WITH NATIVE GOLD AND OTHER METALS - Novgorodova M.I.; Boronikhin V.A.; Generalov M.Ye.; Cramer H. (My University, 1989)
Natural finds of native silicon are not numerous. This mineral was identified tentatively by Bird and Weathers only by its X-ray diffraction characteristics in specimens of josephinite from the marginal part of the Josephine serpentinite pluton, California-Oregon state border, USA. The presence of native silicon associated with native gold and other metals in various mineralized rock types indicates that in the early stage the ore-forming fluid systems were sharply reducing in places where the metalliferous fluids were being discharged. In the latter, judging by the presence of graphite and carbides among the minerals studied, carbon played a major role, so the possibility of organic forms of metal migration cannot be excluded.